The “Death of God” and the onto-theological constitution of metaphysics - Restrepo Bermúdez, Carlos Enrique (Estudios de Filosofía, 2007)
Heideggerian interpretation of the “Death of God” in Nietzsche entails the essential importance of a movement according to which Metaphysics is overcome. The said movement is verified in the most influential of modern Philosophies, mostly in the Philosophies of Kant and Hegel. In Heidegger’s words, after Nietzsche “the only road for Philosophy is its perversion and denaturalization, so we have no other alternatives in view for her”. This overcoming jeopardizes the whole of the History of Being that has taken place and enables the discovery, at the heart of the same Metaphysics, of its Onto-Theological constitution. This paper examines the “Death of God” in the light of the postulate of Onto-Theology as Essence of Metaphysics, and the consecuences therefrom derived for the thought of God in ContemporaryvPhilosophy.